The relevance of the meaning of plantain in folk medicine - Anorbayeva Shahzoda Sadriddinovna; Altyboeva Mavsumа Gulyamovna (Genius Journals, 2023)
This article provides information about the significance and harmful properties of the Plantain in folk medicine. The plant (Plantago Major) is a perennial herbaceous plant with a short and thick rhizome belonging to the plant family. 260 types of wheelbarrows are known. There are 6 species in Uzbekistan, 4 of which are used as medicinal plants. The leaves are located in the form of a ball at the root throat, belt, broadly ovate or elliptical, lanceolate or ribbonshaped. Flowers form simple spikes at the ends of stems and branches.
Keywords: Plantain; medicine; vitamins